Analisis Komunikasi Interpersonal dan Etika Hubungan Pertemanan Sebaya - Muhamad Afdoli Ramadoni; Ahmad Jumhan; Muhammad Zainduddin Nawi; Muhammad Idmar Wijaya; Sri Devhi; Mutiara Amalia Indah; Ayesa Azhara (Jurnal Riset Komunikasi Penyiaran Islam, 2026)
Abstract. Interpersonal communication plays a crucial role in shaping the quality of peer friendships in a college setting. However, students’ social interactions still face various challenges, such as low empathy, sarcastic behavior, the spread of gossip, and conflicts arising from communication misunderstandings. These phenomena are also observed among students at Raden Fatah State Islamic University in Palembang, who uphold Islamic ethical values and communication norms. This study aims to analyze the relationship between interpersonal communication and peer friendship ethics among students. The study employs a descriptive qualitative approach, with data collected through in-depth interviews, observations, and documentation involving 101 students. The results indicate that effective interpersonal communication is associated with empathetic attitudes, openness, mutual respect, and the ability to resolve conflicts constructively. Conversely, poor interpersonal communication has the potential to cause misunderstandings, the spread of negative information, and strained social relationships. The novelty of this study lies in its examination of the relationship between interpersonal communication and friendship ethics within the context of an Islamic university. This study recommends strengthening education in communication ethics and social skills to foster harmonious and mutually respectful relationships among students. Abstrak. Komunikasi interpersonal berperan penting dalam membentuk kualitas hubungan pertemanan sebaya di lingkungan perguruan tinggi. Namun, interaksi sosial mahasiswa masih menghadapi berbagai permasalahan, seperti rendahnya empati, perilaku saling menyindir, penyebaran gosip, dan konflik akibat kesalahpahaman komunikasi. Fenomena ini juga ditemukan pada mahasiswa Universitas Islam Negeri Raden Fatah Palembang yang menjunjung nilai etika dan komunikasi Islami. Penelitian ini bertujuan menganalisis hubungan komunikasi interpersonal dengan etika pertemanan sebaya mahasiswa. Penelitian menggunakan pendekatan kualitatif deskriptif dengan data yang diperoleh melalui wawancara mendalam, observasi, dan dokumentasi terhadap 101 mahasiswa. Hasil penelitian menunjukkan bahwa komunikasi interpersonal yang baik berkaitan dengan sikap empati, keterbukaan, saling menghargai, serta kemampuan menyelesaikan konflik secara konstruktif. Sebaliknya, komunikasi interpersonal yang rendah berpotensi menimbulkan kesalahpahaman, penyebaran informasi negatif, dan renggangnya hubungan sosial. Kebaruan penelitian terletak pada kajian hubungan komunikasi interpersonal dan etika pertemanan dalam konteks perguruan tinggi Islam. Penelitian ini merekomendasikan penguatan pendidikan etika komunikasi dan keterampilan sosial untuk menciptakan hubungan mahasiswa yang harmonis dan saling menghormati.